Gonadotropin-relasing hormone agonist (GnRH-a) induces apoptosis and reduces cell proliferation in eutopic endometrial cultures from women with endometriosis - Meresman, Gabriela Fabiana (2003)
There is growing evidence that suggests a direct action of gonadotropin-releasing hormone agonist (GnRH-a) on endometrial growth. Consequently, our purpose was to evaluate the effect of GnRH-a on in vitro eutopic endometrial cell growth and apoptosis.Prospective study.